Hubungan antara persepsi perawat tentang hubungan interpersonal perawat-dokter dengan stres kerja perawat - Hartono Wahyudi Istiono dan Sri Setiyarini (Berita Kedokteran Masyarakat (BKM), 2005)
Background: Interpersonal relationships between nurse and doctor can be representing as stress resource within nursing workplace. In The United State of America stress in workplace increased up to 70% and spent $ 200-300 billion a year (ICN, 2002). Therefore, nurse have to own the ability and skill of good interpersonal relationships. Purpose: The purpose of this study was to explore the correlation between nurses' perception of nurses and doctor's interpersonal relationship and stress within nursing workplace in Cendana inpatient ward in Dr. Moewardi Hospital, Surakarta. Study method: This study utilized descriptive and non experimental method with a cross-sectional instrument. The subject of this study was 50 nurses which is the total population of nurses in Cendana ward in Dr. Moewardi Hospital, Surakarta. The data were collected by the closed questionnaire. The data was analyzed with the correlation of Kendall's Tau. The study was conducted in November 2004. Study finding: Related to the doctors and nurses' interpersonal relationship in Cendana ward, Dr. Moewardi Hospital, 12 % respondents of the study stated that is in very good category, and 58% respondents stated good. However, 28% respondents stated that the doctors and nurses' interpersonal relationship in Cendana ward is poor and 2% of respondents stated bad. Stress of nursing workplace that is in very low category is 12%, in medium stress is 20%, in low stress is 14 %, and in high stress is 2%. Based on the statistical tests, there was a significant correlation between nurses and doctors' interpersonal relationship and stress of nursing workplace in Cendana Ward, Dr. Moewardi Hospital (p = 0.001‹ 0.025 and r = 0.406). Summary: The nurses and doctors' interpersonal relationships are mostly in good category, and most of the respondents feel that the stress is decreasing. There is a significant correlation between the perceived nurses and doctors interpersonal relationship with stress in the nursing workplace in Cendana ward, Dr. Moewardi Hospital, Surakarta. Keywords: interpersonal relationship, stress in workplace